Differences in the Variation of Silencer Media Thickness from Waste Patchwork And Plywood To Reduce The Noise Intensity - Zulpha, Lulu; Djuhriah, Nany; Fikri, Elanda (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
One of the most dangerous environmental factors is noise, which is crucial to control. This research aims to determine the differences in silencer media thickness between patchwork and plywood offsets to reduce noise intensity in cutting yarn engines. The method study characteristic experiment with design research conducted in this study used a design pretest-posttest without control. The population in this study is the whole room production source producing intensity noise by PT Trisula Textile Industries. Sample in the study This machine is cutting yarn, which produces the most noise. Purposive sampling is the technique used to conduct sample studies. e in six repetitions, with 36 temperature and moisture measurements. The measurement of the intensity of noise at the source of noise before being given treatment ranged from 97.26 to 97.43. The results of the decline in noise intensity after a given silencer show that variation 1 decreased the average by 5.66%, variation 2 decreased the average by 8.89%, and variation 3 lowered the average by 11.89% dB. We processed the data using the one-way ANOVA test, and the results showed a P value of 0.0001 (significant), which is less than 0.05, which indicates a significant difference in each variation of thickness. Industry can use thicker plywood thickness boards if applied in areas with a higher noise level and install a wheel on a tool reducer that can be used practically. Further, researchers can use different types of damping media and vary the thickness of the cloth patch.